Quest for the Donor Star in the Magnetic Precataclysmic Variable V1082 Sgr - Tovmassian, G. (2018)
We obtained high-resolution spectra and multicolor photometry of V1082 Sgr to study the donor star in this 20.8 hr orbital period binary, which is assumed to be a detached system. We measured the rotational velocity (v sin i = 26.5 ± 2.0 km s-1), which, coupled with the constraints on the white dwarf mass from the X-ray spectroscopy, leads to the conclusion that the donor star barely fills 70% of its corresponding Roche lobe radius. It appears to be a slightly evolved K2-type star. This conclusion was further supported by a recently published distance to the binary system measured by the Gaia mission. At the same time, it becomes difficult to explain a very high (≤10-9 Ṁ yr 1) mass transfer and mass accretion rate in a detached binary via stellar wind and magnetic coupling.